Edukasi Masyarakat Sebagai Upaya Pencegahan Keluhan Low Back Pain (LBP) di Puskesmas Balung - Aisyiyah Alviana Agustin (Indonesian Journal Publisher, 2022)
Low back pain is pain that can be localized that occurs between the costal margins to the inferior gluteal folds that occurs for more than one day and can cause leg pain or numbness. 7.6% to 37% of the Indonesian population has experienced lower back pain. Low back pain can be caused by several risk factors, including age, body mass index (BMI), years of service, work chair, sitting position and exercise habits. Understanding low back pain and living a healthy life is one of the keys to success in preventing and solving low back pain problems. So it is important for the community at the Balung Health Center to understand about low back pain and live a healthy life. Therefore, it is necessary to increase knowledge and understanding in the community about low back pain and healthy living through education and distribution of leaflets at the Mahoni 41, 45 and 93 Integrated Health Centers in Balung, Jember Regency. This community service was carried out in May-June 2022. Patients were checked for height, weight, abdominal circumference, blood pressure and blood sugar levels. Based on the evaluation results through the pre test and post test, there were 32 people (76.1%) on Mahogany 41, 40 people (80%) on Mahogany 45 and 32 people (72.9%). This shows that there is an increase in understanding of low back pain. So it is hoped that with this knowledge, the community can apply it in daily life for a healthy lifestyle so as not to experience complaints of low back.